1996
DOI: 10.1002/hep.510240215
|View full text |Cite
|
Sign up to set email alerts
|

The peptide-based thrombin inhibitor CRC 220 is a new substrate of the basolateral rat liver organic anion-transporting polypeptide

Abstract: The peptidomimetic thrombin inhibitor CRC 220, 4-methoxy-2,3,6-trimethylphenylsulfonyl-L-aspartyl-D-4-amidinop henylalanyl- piperidide, is taken up into isolated rat hepatocytes through active, carrier-mediated transport. This uptake is inhibited by bile acids. Functional expression in Xenopus laevis oocytes was performed to identify the transport system responsible for the hepatocellular CRC 220 uptake. Injection of poly(A)+RNA in X. laevis oocytes resulted in a two- to three-times higher uptake of CRC 220, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…3 Rapid hepatic Oatp1-mediated uptake has been already previously suggested to limit the oral bioavialability of the thrombin inhibitor, CRC 220. 32 In conclusion, this study demonstrates that rifamycin SV and rifampicin exhibit differential inhibition of the hepatic organic anion transporting polypeptides, Oatp1 and Oatp2, and that rifampicin is a selective inhibitor of Oatp2. Although additional studies with more recently cloned members of the Oatp family (e.g., liver-specific transporter, Lst-1 33 ) must be performed, the data suggest that rifamycin SV and rifampicin could be used to determine the in vivo relevance of Oatp1 and Oatp2 for the bioavailability and disposition of amphipatic xenobiotic compounds undergoing efficient hepatic elimination and excretion into bile.…”
Section: Fig 1 Inhibition Of Oatp1 Andmentioning
confidence: 57%
“…3 Rapid hepatic Oatp1-mediated uptake has been already previously suggested to limit the oral bioavialability of the thrombin inhibitor, CRC 220. 32 In conclusion, this study demonstrates that rifamycin SV and rifampicin exhibit differential inhibition of the hepatic organic anion transporting polypeptides, Oatp1 and Oatp2, and that rifampicin is a selective inhibitor of Oatp2. Although additional studies with more recently cloned members of the Oatp family (e.g., liver-specific transporter, Lst-1 33 ) must be performed, the data suggest that rifamycin SV and rifampicin could be used to determine the in vivo relevance of Oatp1 and Oatp2 for the bioavailability and disposition of amphipatic xenobiotic compounds undergoing efficient hepatic elimination and excretion into bile.…”
Section: Fig 1 Inhibition Of Oatp1 Andmentioning
confidence: 57%
“…Coadministration of an OATP inhibitor could be used to increase the oral bioavailability of drugs with excessive OATP-mediated hepatic first-pass elimination such as, for example, the thrombin inhibitor CRC 220. 32 On the other hand, a coadministration of an OATP inhibitor could reduce the liver uptake of intrahepatically active drugs such as pravastatin 8,13 and, thus, lead to a decrease of drug efficacy and possible therapeutic failure. Furthermore, the development of specific inhibitors for individual Oatps/OATPs could help to explore the relevance of selective Oatps/OATPs for pharmacokinetics and adverse drug reactions during preclinical and clinical drug development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several peptidomimetic drugs such as enalapril [15], temocaprilat [16] and CRC220 [17], as well as cyclic (BQ123) [14] and linear (deltorphin) [18] peptides, are substrates of this growing family of membrane-transport proteins. A comparison between Oatp1, Oatp2 and the human OATP (OATP-A) revealed that the magnetic-resonance-imaging agent gadoxetate was only transported by Oatp1 [19], whereas digoxin was a specific compound for Oatp2 [3].…”
Section: Introductionmentioning
confidence: 99%